Estrategias de aprendizaje que utilizan estudiantes de quinto de primaria en un curso de informática. - Rodríguez Rojas, Marly (Universidad Antonio Nariño, 2021)
The use of ICT and digital literacy is a new and innovative scenario for many students in the Colombian context. Entering this world not only requires them to put into play special skills, but it is also possible to enhance others skills that have to do with their personal development and learning processes. This work aims to determine what study strategies students use in the academic space of computer classrooms in a school of the public network of the Bogotá city. The group of investigated students has the characteristic of being a population without access to computer resources in their homes. The methodology is based on the application of an analysis instrument called inventory of study and learning strategies. Through its application, the interest of students in computer tools has been verified despite their difficulties in accessing the appropriate instruments to optimize the development of their practices.